Estimating passage kinetics using fibre-bound 15N as an internal marker - Huhtanen, Pekka; Hristov, Alex (Elsevier, 2001)
Acid detergent insoluble N (ADF-N) is resistant to microbial and mammalian enzymes and natural labeling of ADF-N with 15N could provide an internal marker for digesta passage kinetics studies. Two late-lactation ruminally and duodenally cannulated Holstein cows were used to evaluate fibre-bound 15N as passage kinetics markers. The cows were fed ad libitum on 70% forage:30% concentrate diets based either on lucerne hay (LH) or lucerne silage (LS). A pulse dose of lucerne intrinsically labeled with 15N, applied as (15NH4)2SO4 fertilizer, was given in addition to lucerne in the diet. Duodenal (n=17) and faecal (n=14) grab samples were collected for 72 h. The samples were analyzed for 15N-enrichment of neutral detergent fibre-bound N (NDF-15N) and acid detergent fibre-bound N (ADF-15N). Kinetic parameters were estimated using two-compartmental models comprised of either two age-independent compartments (G1 G1) or one gamma age-dependent and one age-independent compartment (Gn G1, n=2¯4). The models with an age-dependency in the first compartment improved curve-fitting and explained on average 0.99 of the variation in NDF-15N and ADF-15N-enrichment. Total mean residence time (TMRT) of NDF-15N was shorter (P<0.05) than that of ADF-15N (40.2 versus 47.0 h). This suggests that part of the available fibre-bound N (NDF-15N minus ADF-15N) was digested and therefore NDF-15N does not satisfy the requirements of an ideal passage kinetics marker. Pre-duodenal sites accounted for 0.91 of compartmental mean residence time (CMRT) estimated from faecal sampling, suggesting that pre-duodenal compartments accounted for the majority of the ascending phase of marker excretion curve. The values of time delay, CMRT and TMRT for ADF-15N of 7.7, 39.3 and 47.0 h were within the range reported for external markers for cows fed at similar level of DM intake. The results from this study suggest that ADF-15N has significant potential as an internal passage kinetics marker. As compared to the commonly used external markers ADF-15N has the advantage that it does not modify the digestibility or flow characteristics of labeled particles.
Keywords: Ko; märehtijät; ruuansulatus; typpi; passage kinetics; markers; fibre-bound 15N